2010
DOI: 10.1007/s13181-010-0068-8
|View full text |Cite
|
Sign up to set email alerts
|

Local Antivenom Treatment for Ophthalmic Injuries Caused by a Naja atra

Abstract: We report a case of local antivenom therapy for ocular exposure to the venom of Naja atra. An 83-year-old woman sustained conjunctival and corneal injuries by the venom of a spitting N. atra. Local instillation of N. naja antivenom quickly relieved the pain as measured by visual analog scale, and she recovered uneventfully. Good recovery ensuing topical antivenom administration for ocular exposure to the venom of spitting N. atra and Naja nigricollis has been described in literature, but the pain response was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…They observed that cobras perform rapid cephalic oscillations to coordinate the target’s movements, for increasing the chance of hitting the eyes. Due to high occurrences of venom spitting on the eye, we review cases of venom-spit ophthalmia by cobras in Asia [ 3 , 9 , 10 ], Africa [ 3 ], and United States [ 11 ] as well as by rattlesnakes in the United States [ 12 , 13 , 14 ] ( Table 1 ).…”
Section: Snake Venom/toxin Cause Ocular Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed that cobras perform rapid cephalic oscillations to coordinate the target’s movements, for increasing the chance of hitting the eyes. Due to high occurrences of venom spitting on the eye, we review cases of venom-spit ophthalmia by cobras in Asia [ 3 , 9 , 10 ], Africa [ 3 ], and United States [ 11 ] as well as by rattlesnakes in the United States [ 12 , 13 , 14 ] ( Table 1 ).…”
Section: Snake Venom/toxin Cause Ocular Complicationsmentioning
confidence: 99%
“…Although no children were reported in Taiwan, snake venom spitting was also considered one of the causes of eye burn in children in other courtiers [ 15 ]. Another venom-spit ophthalmia by N. atra was reported from an 83-year-old woman in Hong Kong while she was trying to kill the cobra [ 9 ]. After being treated with 0.5% chloramphenicol and 0.12% prednisolone eye drops, she went home without severe symptoms.…”
Section: Snake Venom/toxin Cause Ocular Complicationsmentioning
confidence: 99%
“…Also, diluted antivenom was instilled in her eyes, which interestingly gave a substantial pain reduction. [ 16 ] One herpetologist has been spat in the same eye by three different types of captive spitting cobra ( H. haemachatus, N. atra , and Naja pallida ) at different occasions. Direct irrigation with tap water for 1–2 h helped in all cases.…”
mentioning
confidence: 99%